Differences between female suicidal patients with family history of suicide attempt and family history of completed suicide - Rodante, Demián (2016)
Background: Family history of suicidal behavior and suicide are both risk factors for suicide. However, the effects of family history of suicide versus suicide attempts on patient suicidal behavior remain unclear. The aim of the present study was to understand if family history of suicide as compared to family history of suicide attempts or no family history of suicidal behavior evidences different associations with suicidal behavior among psychiatric patients. Method: Participants included 157 female patients between the ages of 18 and 65 years admitted at the Dr. Braulio A. Moyano Neuropsychiatric Women's Hospital. Results: Seventy-nine patients (50.3%) reported no family history of suicidal behavior (NFHSB), while 78 patients (49.7%) reported a family history of suicidal behavior. Specifically, 41 patients (26.1%) reported a family history of suicide attempt (FHSA) and 37 patients (23.6%) reported a family history of suicide (FHS). These groups showed significant differences between family history of psychopathology and number of previous suicide attempts. Patients with an FHSA were more likely to present with a greater number of previous suicide attempts as compared to patients with NFHSB and FHS. Conclusion: There is an association between the number of suicide attempts and family history of suicide attempts in female patients hospitalized for suicidal behavior.